Postgraduate forensic science education in Turkey - (:unkn) unknown (AMER SOC TESTING MATERIALS, 1996)
Legal medicine in Turkey, has an educational background that goes back to 1839 and the first autopsy in modem terms was performed in 1841. In the early days, it was common practice for those involved in this work to extend their investigative knowledge into areas not directly concerned with medical matters. However forensic medical investigations cannot be entrusted in the hands of single investigators, but should rather be dealt with by cooperative groups of experts nowadays. This need was the major force for the establishment of the Institute of Legal Medicine and Forensic Sciences by a special article of the law ( 2547) as a training and research center in 1982. The Institute being the first and only institution giving master's and doctorate degrees in Forensic Sciences, has 3 major departments: 1) Medical Sciences Department, 2) Basic Sciences Department and 3) Social Sciences Department. Graduates of various fields ranging from medical doctors specialized in any field, biologists, chemists to lawyers, district attorneys, psychologists and other related fields are composing the multidisciplinary structure of the institute. The main research fields of the Institute are: population genetics, paternity investigation, child abuse, and identification of human remains.
Keywords: forensic science; education; postgraduate education; Turkey